Challenges and barriers to sustainable energy consumption in the Silesian Voivodeship - Słupik, Sylwia (Economic and Environmental Studies, 2020)
One of the main factors in achieving the ecological development goals is the change of unsustainable consumption patterns. Households play here a crucial role. The high level of urbanization and industrialization in the Silesian Voivodeship has caused serious environmental degradation, which in its turn has led to deterioration of the living conditions. These conditions mean it is particularly important to use natural resources in a rational and efficient manner and in line with the principles of sustainable development. The purpose of this paper is to characterize the developmental paths and identify the main factors that hinder sustainable energy consumption in the Silesian Voivodeship. Furthermore, the author assessed the awareness level and decisions households make in relation to energy consumption in the region, in the context of sustainable development. Data included in this article comes from surveys concerning development of the ecological goods and services market, which were conveyed in 2013 and 2014.